Ethical and legal challenges associated with disaster nursing. (June 2015) - Aliakbari, Fatemeh; Hammad, Karen; Bahrami, Masoud; Aein, Fereshteh
Background: In disaster situations, nurses may face new and unfamiliar ethical and legal challenges not common in their everyday practice. Research question/objectives/hypothesis: The aim of this study was to explore Iranian nurses' experience of disaster response and their perception of the competencies required by nurses in this environment. Research design: This article discusses the findings of a descriptive study conducted in Iran in 2012. Participants and research context: This research was conducted in Iran in 2012. Participants included 35 nurses who had experience in healthcare delivery following a disaster event in the past 10 years, either in a hospital or out-of-hospital context. Ethical considerations: This research study was approved by the Ethics Committee of the Isfahan University of Medical Sciences. Findings: From this study, five themes emerged as areas that nurses require competence in to work effectively in the disaster setting. This article focusses on one theme, the ethical and legal issues that arise during disaster response. Within the theme of ethical and legal issues, two sub-themes emerged. (1) Professional ethics explores professional responsibility of nurses as well as sense of ethical obligation. (2) Adherence to law refers to nurses' familiarity with and observation of legal requirements. Discussion: This article adds to a growing pool of literature which explores the role of nurses in disasters. The findings of this study emphasize the need for nurses working in the disaster setting to be aware of professional responsibilities and familiar with legal requirements and the challenges related to observing ethical responsibilities. Conclusion: In highlighting these issues, this article may provide a useful starting point for the development of an educational framework for preparing nurses and other health professionals to work in the disaster setting.